Dioscin alleviates lipopolysaccharide-induced inflammatory kidney injury via the microRNA let-7i/TLR4/MyD88 signaling pathway. (September 2016) - Qi, Meng; Yin, Lianhong; Xu, Lina; Tao, Xufeng; Qi, Yan; Han, Xu; Wang, Changyuan; Xu, Youwei; Sun, Huijun; Liu, Kexin; Peng, Jinyong
Graphical abstract: Abstract: We previously reported the potent effect of dioscin against renal ischemia/reperfusion injury, but little is known about the role of dioscin in lipopolysaccharide (LPS)-induced inflammatory kidney injury. The present work aimed to investigate the effects and potential mechanisms of dioscin in preventing LPS-induced kidney injury. In vivo injury was induced in rats and mice with an intraperitoneal injection of LPS (10 mg/kg), and in vitro studies were performed on NRK-52E and HK-2 cells challenged with LPS (0.5 μg/ml). Our results indicated that dioscin significantly protected against renal damage by decreasing blood urea nitrogen and creatinine levels and reversing oxidative stress. Mechanistic studies demonstrated that dioscin markedly up- regulated the level of the microRNA let-7i, resulting in significant inhibition of TLR4 expression. Dioscin significantly down-regulated the levels of MyD88, NOX1 and cleaved caspase-8/3; inhibited the nuclear translocation of NF-κB; inhibited PI3K and Akt phosphorylation; increased the levels of SOD2; and decreased the mRNA levels of IL-1β, IL-6, MIP-1α, Fas and FasL. In vitro, transfection of microRNA let-7i inhibitor and TLR4 DNA were applied, and the results further confirmed the nephroprotective effect of dioscin in suppressing TLR4/MyD88 signaling and subsequently inhibiting inflammation, oxidative stress and apoptosis. Furthermore, the abrogation of cellular MyD88 expression by ST2825 eliminated the inhibitory effect of dioscin on the levels of nuclear NF-κB, cleaved caspase-3, SOD2 and ROS. These data indicated that dioscin exerted a nephroprotective effect against LPS-induced inflammatory renal injury by adjusting the microRNA let-7i/TLR4/MyD88 signaling pathway, which provided novel insights into the mechanisms of this therapeutic candidate for the treatment of inflammatory kidney injury.